MOLECULAR ADSORPTION OF ZEA MAYS LEAF PHYTOCHEMICALS ON Fe(110) AS CORROSION INHIBITORS: DFT AND MONTE CARLO STUDY - Syarif Hidayatullah; Suteja Suteja (Scientific Journal of Mechanical Engineering Kinematika, 2026)
Plant-derived compounds have attracted increasing attention as environmentally friendly corrosion inhibitor candidates. However, the molecular adsorption behavior of selected phytochemicals from Zea mays leaves on iron surfaces remains insufficiently understood. This study investigates ethyl palmitate (EP), hexadecanoic acid (HA), and 9,12,15-octadecatrienoic acid (OA), identified from Zea mays leaf extract, as potential inhibitors for the Fe(110) surface. Density Functional Theory (DFT) calculations at the B3LYP/6–311G(d,p) level were used to evaluate global and local electronic descriptors, including frontier molecular orbital energies, energy gap, dipole moment, hardness, softness, electronegativity, electron transfer tendency, Mulliken charge distribution, electrostatic potential, and Fukui indices. Monte Carlo simulations were performed to examine the adsorption behavior of these molecules on Fe(110) in the presence of water molecules. The DFT results showed that OA had the smallest energy gap and the highest softness, indicating the strongest electronic reactivity among the studied molecules. In contrast, EP exhibited the strongest adsorption affinity in the Monte Carlo simulation. The calculated differential adsorption energies for EP, OA, and HA were −203.32, −192.71, and −189.69 kcal/mol, respectively, indicating favorable adsorption on Fe(110). Oxygen-containing functional groups were identified as the main reactive sites involved in molecule–surface interactions. The main contribution of this work is the molecular-level comparison of selected Zea mays leaf phytochemicals on Fe(110) using combined DFT and Monte Carlo approaches. The results suggest that EP and OA are promising green corrosion inhibitor candidates, although experimental validation is required to confirm their inhibition efficiency under practical corrosive conditions.